The effect of various jaw motor tasks on body sway - Hellmann, Daniel; Giannakopoulos, Nikolaos Nikitas; Blaser, Ralf; Eberhard, Lydia; Schindler, Hans J. (Journal of oral rehabilitation, 2011)
Alterations of body sway caused by isometric contractions of the jaw muscles have been reported previously. The objective of this study was to test if motor tasks of the masticatory system with different control demands affect body posture differently during quiet stance. Position and sway displacements of the center of foot pressure (COP) were measured for 20 healthy subjects who either kept the mandible at rest or performed unilateral and bilateral maximum voluntary teeth clenching, feedback-controlled biting tasks at submaximum bite forces, or unilateral chewing. Two weeks later the measurements were repeated. Compared with quiet stance, the COP results revealed significant changes during the feedback-controlled biting tasks. Robust sway reduction and anterior displacement of the COP were observed under these conditions. Body oscillations were not significantly affected by maximum bites or by unilateral chewing. For most of the variables investigated there were no significant differences between unilateral and bilateral biting. Robust sway reduction during feedback-controlled biting tasks in healthy subjects involved a stiffening phenomenon that was attributed to the common physiological repertoire of posture control, and might optimize the stability of posture under these conditions.
First published: 09 March 2011
Gesehen am 04.10.2022